Analisis Kelengkapan Pengisian Catatan Perkembangan Pasien Terintegrasi Dokter Pada Rekam Medis Elektronik Assesmen IGD Di RSUD Tarakan Tahun 2024 - Arif Ibnu Fadillah; Bangga Agung Satrya; Noor Yulia; Muhammad Fuad Iqbal (Jurnal Medika Nusantara, 2025)
Integrated Patient Progress Notes (CPPT) are activities of health workers (doctors, nurses, pharmacists, nutritionists, and other officers) in recording the results of their activities, in one format together in the patient's medical record related to the patient's care process. This sheet contains the patient's identity, date of examination, examination time, notes from the treating doctor, notes from other clinical staff, and is verified with the initials and name of the officer who filled it in. All actions taken are recorded at the time, date and type of action given and must be signed by the examining doctor. This study aims to see the completeness of the doctor's integrated patient progress notes in the electronic medical record of the IGD assessment at Tarakan Hospital, Jakarta. This study uses a descriptive methodology with a quantitative approach. A sample of 77 electronic medical records of the IGD assessment used random sampling. Research results: from the analysis, the completeness was 90%, not reaching the minimum standard set by the Ministry of Health, which is 100%. Of the 4 components analyzed, the highest level of completeness is in the patient identification, authentication, good recording components of 100%, while the lowest percentage of completeness is in the important report content component of 93%. Several factors that cause poor doctor CPPT are when the doctor has filled in the Doctor CPPT but the system does not save it because an error occurs. It is recommended that the system be monitored consistently to prevent such errors during data entry, and that a special computer unit for doctors be created to minimize waiting time when interacting with other nursing staff.